Laryngopharyngeal reflux in war-torn Syria and its association with smoking and other risks: an online cross-sectional population study - Kakaje, Ameer (BMJ Open, 2020)
OBJECTIVES: To demonstrate the burden of laryngopharyngeal reflux (LPR) in Syria and its associated variables. DESIGN: This is a cross-sectional study that used online questionnaires that included demographics, smoking, war-related questions and reflux symptom index (RSI). SETTING: This research was conducted online across Syria and included the general population. PARTICIPANTS: Participants who lived in Syria, agreed to participate, and responded to all the RSI questions were included. This research comprised 734 participants, with 94.6% response rate, 75.5% being females, and a mean age of 24 years. RESULTS: Overall, 31.9% of subjects had symptoms suggestive of LPR. Participants who were 30 years and younger had fewer symptoms suggestive of LPR compared with the older group p=0.012 (OR 0.534; 95% CI 0.325 to 0.877). While having an epigastric burning sensation, chest pain and indigestion were the most common symptoms, having a sore throat was the least common. Being distressed from war noises was associated with more symptoms p=0.009 (OR 1.562; 95% CI 1.117 to 2.183). However, losing someone or changing place of living due to war were not significantly associated with these symptoms p>0.05. RSI scores were associated with cigarette and/or shisha smoking p<0.05. Finally, asthma, allergic disorders and having a job were associated with having LPR symptoms p<0.05. No significant findings were observed in consanguinity, marital status, educational level and socioeconomic status. CONCLUSIONS: War, smoking, asthma, allergies, respiratory conditions and having a job were associated with LPR symptoms. However, they may be associated with these symptoms independently from LPR; for instance, similar symptoms can be caused by the mental disorders from war, the unique environment and irritant substances of the laryngeal mucosa.